2013
DOI: 10.5714/cl.2013.14.4.247
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-layer assembled graphene oxide films and barrier properties of thermally reduced graphene oxide membranes

Abstract: In this study, we present a facile method of fabricating graphene oxide (GO) films on the surface of polyimide (PI) via layer-by-layer (LBL) assembly of charged GO. The positively charged amino-phenyl functionalized GO (APGO) is alternatively complexed with the negatively charged GO through an electrostatic LBL assembly process. Furthermore, we investigated the water vapor transmission rate and oxygen transmission rate of the prepared (reduced GO [rGO]/rAPGO) 10 deposited PI film (rGO/rAPGO/PI) and pure PI fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
43
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(54 citation statements)
references
References 25 publications
8
43
2
1
Order By: Relevance
“…The background subtracted Raman spectra shown in Figure S4 confirmed the successful preparation of GO, cGO, and cGO–PAN composite nanofibers by examining the ratio of D- and G-bands. While the D/G peak ratio for the bare GO was examined to be 0.88, which was within the literature values [ 41 , 42 , 43 , 44 ], the ratio slightly increased to 0.92 and 0.93 upon modification with CTAC and PAN, respectively. It has been reported that the modification of GO (e.g., covalent organic/polymer modifier and chemical doping) often leads to a notable increase of the D-band (i.e., more defects and disordered structure), resulting in the increase of the D/G ratio [ 43 , 44 ].…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The background subtracted Raman spectra shown in Figure S4 confirmed the successful preparation of GO, cGO, and cGO–PAN composite nanofibers by examining the ratio of D- and G-bands. While the D/G peak ratio for the bare GO was examined to be 0.88, which was within the literature values [ 41 , 42 , 43 , 44 ], the ratio slightly increased to 0.92 and 0.93 upon modification with CTAC and PAN, respectively. It has been reported that the modification of GO (e.g., covalent organic/polymer modifier and chemical doping) often leads to a notable increase of the D-band (i.e., more defects and disordered structure), resulting in the increase of the D/G ratio [ 43 , 44 ].…”
Section: Resultssupporting
confidence: 79%
“…While the D/G peak ratio for the bare GO was examined to be 0.88, which was within the literature values [ 41 , 42 , 43 , 44 ], the ratio slightly increased to 0.92 and 0.93 upon modification with CTAC and PAN, respectively. It has been reported that the modification of GO (e.g., covalent organic/polymer modifier and chemical doping) often leads to a notable increase of the D-band (i.e., more defects and disordered structure), resulting in the increase of the D/G ratio [ 43 , 44 ]. The marginal increase of D/G ratios for our cGO and cGO–PAN composite nanofibers could be due to the relatively weak modification between the GO and the modifiers via electrostatic and physical interactions.…”
Section: Resultssupporting
confidence: 79%
“…In addition, titanium glycolate was transformed to TiO 2 by hydrolysis. We assume that although thiol-functionalized graphene wrapped titanium glycolate presents new properties, the thin graphene oxide layer induces good water transmittance to the new composite [37,38]. The presence of amorphous TiO 2 and gold was confirmed from the XRD pattern and EDS analysis shown in Fig.…”
Section: Resultsmentioning
confidence: 77%
“…32 Meanwhile, the low I D /I G value of graphene veries that the sample is graphene rather than graphene oxides (GO) since the ratio of I D /I G for GO is close to 1.0. 33 Second, the 2D band shis from 2762 cm À1 to 2711 cm À1 , and the G band shis from 1585 cm À1 to 1588 cm À1 for graphene and Ag/graphene, respectively. This can be attributed to the inuence of electron properties during the double resonance process, 34,35 and indicates n-doping of graphene with Ag deposition.…”
Section: Resultsmentioning
confidence: 97%